Characterisation of p52-regulated lncRNAs in multiple Myeloma - Yei, Xi (Nanyang Technological University, 2022)
Multiple Myeloma (MM) is a rare form of hematologic malignancy characterized by the abnormal growth of plasma cells. MM has multiple evolutionary stages starting from monoclonal gammopathy of undetermined significance (MGUS) evolving to an intermediate stage called “smouldering” MM (sMM), and finally leading to active MM stage. MM cells are reported to display aberrant activation of non-canonical NF-κB pathway via various inhibitory and activating mutations. Additionally, dysregulated expression of non-coding RNAs is also reported in many cancer types including MM. Hence, this project serves to uncover the relationship between the aberrant activation of non-canonical NF-κB pathway and the dysregulated expression of long non-coding RNAs (lncRNAs) in MM. Preliminary data from the lab identified several MM enriched p52-dependent lncRNAs from which we selected two novel lncRNAs for this study. We characterized both lncRNAs in relation to their expression, isoform variants and subcellular localization. Further, their functional importance was studied using both Loss-of-Function (LOF) and Gain-of-Function (GOF) approaches. shRNA based knockdown, CRISPR-Cas9 based Transcriptional Start Site (TSS) Deletion and overexpression studies were done to study the functional importance of the two lncRNAs on MM progression. Interestingly, the first lncRNA was found to enhance proliferation of MM cells whereas the functional role of the second lncRNA requires further experimental validation.